Lived experiences of mothers with newborns lodging at a public hospital in South Africa: A qualitative study - Matshediso Julia Ntuli; Cynthia Spies (Tehran University of Medical Sciences, 2024)
Background & Aim: The challenges of mothers residing at hospital while their ill babies are admitted to a neonatal care unit are understudied and poorly documented. Unfavorable living arrangements and tension between mothers and staff can disrupt their well-being and create feelings of helplessness. This study explored how mothers experienced having to stay at a lodging residence of a public hospital while their newborns were admitted to a neonatal care unit. Methods & Materials: This qualitative content analysis study was conducted through face-to-face, in-depth interviews between March 2021 - April 2021. Data were gathered from 13 mothers who lodged at a public hospital for at least two weeks, were able to speak Sesotho, English, and/or Afrikaans, and were above 18 years of age. Data were analyzed using Tesch's eight steps in the coding process. Results: Data analysis resulted in five categories, each with subcategories. The main categories are "Lodging environment", "Emotional experiences", "Nursing care of babies", "Interaction with staff", and "Participant perspectives". Participants' ages ranged between 23 and 37 years. Three participants had a spouse while the other ten were unmarried and were single parents. Conclusion: The mothers were not optimistic about their lodging experiences, the nursing care of their newborns, and their interaction with healthcare professionals. Hence, they require intervention to alleviate conditions that cause unnecessary stress and anxiety. Health professionals and hospital managers must accommodate the needs of mothers who have no choice but to reside at the hospital when their newborns are admitted for extended periods.